A new species of Eptesicus (Mammalia: Chiroptera: Vespertilionidae) from the Atlantic Forest, Brazil - Miranda, João M.d.; Bernardi, Itiberê P.; Passos, Fernando C. (Zootaxa, 2006)
A new species of the genus Eptesicus Rafinesque (Mammalia: Chiroptera: Vespertilionidae) from Atlantic Forest, Brazil is described. This species is distinct from its congeners based on external and cranial morphometrics, as well as on qualitative traits such as a more reddish coloration, more inflated muzzle and rounder ears.